Fossil priapulid Ottoia from the Kaili biota (Cambrian Series 3) of South China. (2nd June 2016) - Yang, Yuning; Zhao, Yuanlong; Zhang, Xingliang
Abstract : The fossil priapulid Ottoia recovered from the Kaili biota, Cambrian Series 3 and Stage 5 of South China, is the first reported occurrence of the genus outside the Cambrian of Laurentia. A total of 22 specimens are described as Ottoia guizhouensis sp. nov. The new species is distinguished from other Cambrian priapulids, including the type species of Ottoia, O. prolifica Walcott, 1911 from the Burgess Shale, by the introvert that lacks a swollen base and bears a smaller number of longitudinal rows of hooks, and a more elongated trunk with more closely spaced annulations. Anatomically, a probable gizzard, a pair of posterior retractor muscles and muscle fibres of the gut wall are also observed in O. guizhouensis . The presence of the paired retractor muscles can be considered an indication of bilateral symmetry. Gut contents in O. guizhouensis suggest that this animal had an occasional deposit-feeding habit. Specimens buried in life position suggest that Ottoia may have burrowed and wriggled in all directions within the sediment and did not merely make U-shaped burrows. The new occurrence of Ottoia from the Kaili biota sheds new light on the morphology, anatomy and palaeogeographical distribution of this well-known genus, as well as providing new information on the early evolution of priapulids.